Project-Based Islamic Education Learning to Increase Students' Creativity - Qoyimah, Durotul; Hamami, Tasman (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Project-Based Learning (PjBL) is an innovative approach that fosters the creativity and skills of students within Islamic education. This study examines the implementation of PjBL strategies in the context of Islamic education as an effort to enhance students’ creativity. Employing a qualitative approach through library research, this study reviews relevant literature. The findings reveal that PjBL is not only effective in cultivating students’ creativity and active engagement but also strengthens spiritual, moral, and social dimensions through the integration of contextual projects. The implementation of PjBL highlights the shift in the teacher’s role from being a source of information to a facilitator, thereby promoting learning that is more participatory, collaborative, and connected to real-life contexts. Despite challenges such as limited resources, teacher readiness, and curriculum support, this study affirms that PjBL has the potential to serve as a strategic model for shaping visionary, adaptive, and ethically grounded Muslim generations. Thus, this research contributes theoretically by integrating Islamic values into the PjBL framework, and practically by offering guidance for educators in designing meaningful learning experiences that nurture both creativity and noble character.